Non-Verbal Communication Used by University Students’ Examinee in Thesis Proposal Seminar - Rizma, Dian; Zein, T. Thyrhaya; Br. Perangin-angin, Alemina (LingPoet: Journal of Linguistics and Literary Research, 2021)
This thesis entitled Non-Verbal Communication by University Students; Examinee In Thesis Proposal Seminar. Students have a proposal and final thesis examination where they present and explain the research that they have conducted. The researcher interested to provide views and further investigating the meaning of appearance which is expected to obtain a detailed picture of the meaning of non-verbal sign constructed on the meaning of the appearance by semiotic analysis. For this reason, this study aims at 1) To describe the kinds of non-verbal communications used by the student of English Department in the proposal seminar, and 2) To describe the meanings of the non-verbal communications used by the student of English Department in the proposal seminar. The theory of three basic semiotic elements proposed by Peirce (2003) is used to identify the sign action and also determined better the nature and rhetorical function of both verbal and non-verbal representation. The method used in this research is descriptive qualitative. The data of this research are the non-verbal communication of the students from the English department through their Facial Expression, Eye Contacts , Emblems, Adaptors and Body Action. The source of the data obtained one video from the seminar proposal. A semiotic visual image of signs, in the seminar proposal video. There are 7 kinds of non-verbal communication the student showed that obtained and observed by the researcher. The result of this research shows that five types of the non-verbal communications are found in the seminar, i.e. fear, amusement, agony, surprise and disgust. The most dominant type of non-verbal communication is the state of surprise with 2 expressions. Keyword: Non-verbal Communication, Semiotics, Proposal Seminar